2022
DOI: 10.3390/ijerph19031167
|View full text |Cite
|
Sign up to set email alerts
|

The Portuguese Third Version of the Copenhagen Psychosocial Questionnaire: Preliminary Validation Studies of the Middle Version among Municipal and Healthcare Workers

Abstract: A third version of the Copenhagen Psychosocial Questionnaire (COPSOQ III) was developed internationally aiming to respond to new trends in working conditions, theoretical concepts, and international experience. This article aims to present the preliminary validation studies for the Portuguese middle version of COPSOQ III. This is an exploratory cross-sectional study viewing the cross-cultural adaption of COPSOQ III to Portugal, ensuring the contents and face validity and performing field-testing in order to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…Na parte II, foi realizada uma análise descritiva quantitativa das subescalas do COPSOQ III, de modo a analisar a perceção de exposição a fatores psicossociais de risco. A figura 1 apresenta o perfil de risco psicossocial dos colaboradores da administração pública local, através da divisão da pontuação em tercis, que circunscreve o impacto para a saúde que a exposição a determinada dimensão representa (Cotrim et al, 2022). Consideramos como critério de retenção de potencial risco para a saúde todas as subescalas com valor abaixo de 50%, de situação favorável para a saúde (verde).…”
Section: Resultsunclassified
“…Na parte II, foi realizada uma análise descritiva quantitativa das subescalas do COPSOQ III, de modo a analisar a perceção de exposição a fatores psicossociais de risco. A figura 1 apresenta o perfil de risco psicossocial dos colaboradores da administração pública local, através da divisão da pontuação em tercis, que circunscreve o impacto para a saúde que a exposição a determinada dimensão representa (Cotrim et al, 2022). Consideramos como critério de retenção de potencial risco para a saúde todas as subescalas com valor abaixo de 50%, de situação favorável para a saúde (verde).…”
Section: Resultsunclassified
“…In line with this, a Canadian population study found support for dimensions in a short version comprising selected COPSOQ II and III items [ 78 ]. For COPSOQ III, similar approaches have provided general support for dimensions in diverse samples from Turkey [ 79 ], the Netherlands [ 80 ] and Portugal [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COPSOQ is a highly reliable scale for assessing PRFs in the workplace. It is a powerful tool that gathers international consensus on the adequacy for evaluating an extensive and most important psychosocial dimensions [9,[11][12][13][14]. The COPSOQ differs from other scales, since it systematically approaches the interaction between psychosocial work environment and health, not being based and limited to a specific theoretical model, providing a versatility of uses [9,13].…”
Section: Instrumentsmentioning
confidence: 99%